A local and fast interpolation method for mesh deformation. (4th September 2019) - Tang, Jing; Ma, Mingsheng; Li, Bin; Cui, Pengcheng
In this study, a local interpolation approach is developed to deal with the deformation of a mesh containing structured and stretched viscous elements. A new strategy is proposed to compute the local influence distance at each movable mesh point. This strategy not only helps to exclude unnecessary donor points from the computation of the new position of the mesh point, but also gets those viscous elements stiffened appropriately such that they are no longer inverted easily. Further improvements on the efficiency of the proposed algorithm are achieved by parallelising the algorithm and developing a bounding box technique to speed up the procedure of searching donor points. Meanwhile, the robustness of the proposed algorithm in the case of large boundary movement is enhanced by incorporating a state-of-the-art multi-step technique. Various numerical experiments are conducted and the results show that the proposed algorithm could treat cases involving complex boundary movements at a low level of computing consumptions.